Analisis Hasil Tangkapan dan Rantai Pasok dalam Pemasaran Gurita Segar (Octopus Sp.) di Makassar - Kantun , Wayan; Hasbi , Ibnu Malkan; Azrina, Yuli (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
This research aims to analyze the development of catches in maintaining the sustainability of the octopus business and the supply chain in marketing fresh octopus in Makassar. This research was conducted from March to May 2023. The research is classified as a qualitative method with a survey method of fishermen's catches and the marketing supply chain for fresh octopus. The types of octopus caught were Octopus vulgaris and Octopus cyanea with catches reaching 1,000-1,600 kg/trip for 20 days of catching. Fresh octopus marketing supply chain uses channels, margins, and marketing efficiency. In this research, three marketing channel patterns for fresh octopus were obtained: the first is fishermen - consumers, the second is fishermen - retailers - consumers and the third is fishermen - collectors - suppliers - consumers. The most efficient marketing channel is channel three, namely fishermen - traders - collectors - suppliers - and consumers because many suppliers are involved so the marketing margin is high and many profits are made. The third marketing margin has a large profit of IDR. 88,000/kg, the first marketing margin has the lowest profit of IDR 13,000/kg and the second marketing margin is IDR. 25,000/kg. There is development and increase in catches and the formation of several supply chains